O Programa Nacional de Alimentação Escolar (PNAE) e sua relação com a agricultura familiar no município de Guaraniaçu, no período de 2003-2015: um estudo de caso - Cassol, Bruna (2019)
The National School Food Program (popularly known as PNAE in Brazil) is one of the most important public policies for food and nutrition Security (SAN) in Brazil. The implementation of the PNAE over the years has ensured access to food for millions of students throughout the country, during the period in which they are in school. Between the period of 2003-2015, the program underwent a wide reformulation in its structure and management, such as the insertion of the nutritionist as technical responsible and the extension of school meals for students enrolled in daycare centers and education for young people and Adults (EJA). Another important advancement of the PNAE was the implementation of the Law n º 11.947/2009, which ensured the mandatory acquisition of, at least 30% of products of family farming (PA) and settlements of agrarian reform, indigenous communities and Quilombolas for the School lunch. Thus, the present study aimed to analyze the National School Feeding Program (PNAE) and its relationship with family farming (PA), in the municipality of Guaraniaçu-PR, at the Jean Piaget Municipal School and at the Municipal School of Campo Aracy Marques Linares, in the period of 2003-2015. For this, a qualitative research was conducted, involving case study, documental and bibliographic research and field observation. In the field investigation we applied questionnaires and interviews with family farmers, merendeiras, nutritionist, education managers and leaders involved in the dynamics of the PA cooperative, called the Cooperative of Family Agriculture Solidarity of Guaraniaçu (COOAFASG). To ensure interaction with the context of the research, there were visits in schools and in the Permanent Commercialization Center of Family Farming, which is also a place to deliver products for school meals. The collected data were interpreted based on the content analysis in the Minayo thematic modality (2007), which resulted in three thematic categories. It was found that the cooperativism of PA in this city was encouraged and strengthened by public managers. The purchases of foodstuffs for school meals from the PA were 97.87% in the year 2015. Between the years 2010 to 2017, the average acquisition of the products of the PA of the municipality was 64.83%, value above the recommended by Law n º 11.947/2009. The city school presented a higher presence of PA products in the feeding of children, while the school of the field has duality in the modality of teaching, implying difficulties to access the products of PA bought by the state network. The municipality ends up doing the complementarity in school meals with products from the PA. It was also found that the partnership between PA and school feeding promoted rural development for producing families and variety of natural and regional foods on the school menu, as well as the promotion of healthy eating in schools Studied. It is xi therefore considered that the PNAE represents a public policy capable of guaranteeing the formation of healthy eating habits in children, through the consumption of natural foods, fresh and regional, creating habits that can be projected for adulthood.